1982
DOI: 10.1002/jmv.1890090103
|View full text |Cite
|
Sign up to set email alerts
|

Astrovirus‐Associated epidemic gastroenteritis in japan

Abstract: An outbreak of epidemic gastroenteritis associated with astrovirus, the first case reported in Japan, is described. Not only children (5-6 years of age), but also staff members of a kindergarten were affected. the virus particles detected in stools were 28-30 nm in diameter with a circular outline and had the characteristic star-like configuration which allowed identification as astrovirus. Significant immune responses to the virus were confirmed by immune electron microscopy. Out of 84 children, 43 (54.2%) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
39
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 15 publications
(6 reference statements)
3
39
0
Order By: Relevance
“…The incubation period appears to be 24 to 36 hours, similar to those for other gastroenteritis viruses (204). Symptoms can last from 12 h to 3 to 4 days (7,204,210).…”
Section: Astrovirusessupporting
confidence: 54%
See 3 more Smart Citations
“…The incubation period appears to be 24 to 36 hours, similar to those for other gastroenteritis viruses (204). Symptoms can last from 12 h to 3 to 4 days (7,204,210).…”
Section: Astrovirusessupporting
confidence: 54%
“…Children, from infancy to 5 to 7 years of age, are most likely to develop symptomatic disease with astroviruses (7,204,210), although exposed adults can also develop mild disease, but with less frequency (204,210,278). In one study (210), older children were also found to be less likely to develop disease than younger children.…”
Section: Astrovirusesmentioning
confidence: 98%
See 2 more Smart Citations
“…Gastroenteritis outbreaks associated with HAstV infection have been reported in children's day care centers (4,7,10) and schools (12) as well as in care centers for the elderly (9). HAstV infection usually results in mild disease, but outbreaks often involve a high number of children (8).…”
mentioning
confidence: 99%